Telaah Kritis Terhadap Karakteristik Sastra Arab Masa Jahiliyah dan Islam - Ahmad Bachmid (Buletin Al-Turas, 2004)
Arabic Literature contains prose and poetry. Aase consists of Masal speeches (Khatabah, Novels, and Essays (Rasail). So the characteristics of pre-Islamic prose lasted until the Islamic period without any changes on their purposes like loving, appreciating, insisting, encouraging, mourning, and apologizing.